Evaluasi Pengisian Bahan Bakar Khusus Ground Support Equipment (GSE) di Bandar Udara Internasional Jenderal Ahmad Yani Semarang - Sahara, Nurjanah Afdhian; Kona, Musri (SKY EAST: Education of Aviation Science and Technology, 2023)
Ground Support Equipment (GSE) is equipment used to assist with the needs of aircraft during arrival and/or departure, passenger and cargo loading and unloading, as well as mail handling. One common issue that occurs is the spillage of special fuel for GSE, known as fuel spillage, which can disrupt airport operations and pose high safety risks. Therefore, the author conducted research on GSE equipment to identify potential hazards and the efforts made in handling them. This research employed a qualitative method, collecting primary and secondary data through interviews and document collection. The study took place for three months, from January to March 2022, at Jenderal Ahmad Yani International Airport in Semarang. The research findings indicate that there are still many Ground Support Equipment that do not meet the standards for refueling GSE, a lack of dedicated GSE fueling stations, and manual fueling processes that result in numerous risks that can threaten aviation security and safety. The issue of manually refueling Ground Support Equipment can pose dangers to flight security and safety, as well as hinder Ground Handling services and cause airline delays. To avoid these issues, coordination between Apron Movement Control (AMC) personnel and Ground Handling staff is necessary, along with the development of Standard Operating Procedures (SOPs) for refueling GSE, and the construction of dedicated GSE fueling facilities at Jenderal Ahmad Yani International Airport in Semarang.